Incidence, salience, and spillovers: The direct and indirect effects of tax credits on wages - Ghazala Azmat (Quantitative Economics, 2019)
Tax credits are a popular way to alleviate in-work poverty. A common empirical assumption is that the benefit of the tax credit is borne solely by the claimant workers. However, economic theory suggests no particular reason why this should be the case. This paper investigates the impact of the Working Families' Tax Credit, introduced in the UK in 1999, on wages. Unlike similar tax credit policies, this tax credit was paid through employers rather than directly to workers, making it more salient to the employer. Using a novel identification strategy, we can separately identify the effect on wages associated with an increase in the amount of tax credit and that associated with the change in salience. We find evidence that: (1) through the salience mechanism the firm cuts the wage of claimant workers relative to similarly skilled nonclaimants by 30 percent of the tax credit, which is approximately 7 percent of the wage, and (2) there is a negative spillover effect onto the wages of claimant and nonclaimant workers of 1.7 percent, which is approximately 8 percent of the tax credit for claimant workers.
Keywords: I38; J30; H22; H23; 330; Wages; tax credits; incidence; salience